The importance of pharmacokinetics and pharmacodynamics in antimicrobial drug development and their influence on the success of agents developed to combat resistant gram negative pathogens: A review - Palmer, Mary E.; Andrews, Lauren J.; Abbey, Taylor C.; Dahlquist, Ashley E.; Wenzler, Eric (Frontiers in Pharmacology, 2022)
A deep understanding of an antimicrobial’s critical pharmacokinetic and pharmacodynamic properties is crucial towards optimizing its use in patients and bolstering the drug development program. The complexity and rigor of PK and PD studies has improved dramatically in a short time span which has renewed confidence in the value of PK/PD and allowed it to become a fundamental component of a robust drug development program with a high chances of successful approval. A strong and dedicated focus on PK/PD throughout research and development leading the use of an optimized dosing regimen in Phase 3 trials will significantly improve the probability of approval and the confer maximum benefit to the patient for years to come.